Relationship of some mental abilities with the level of performance of young players weightlifting - Ali Lateef, Nibras (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify some mental abilities and their relationship to the level of performance of young players in the weightlifting game.The researchers used the descriptive approach and conducted a sample of the youth clubs (Diyala, Al-Khalis, and Al-Muqdadiya) for the year (2019-2020), who numbered 36 players. By weightlifter research on a group of experts specialized in the field of weightlifting, testing and measuring game, and then conducting the exploratory experiment for the purpose of identifying obstacles to research and then conducting the main experiment, the researchers supervised mental ability tests over a period of three days, from 14/8/2019 to 16/8/2019, during the course of club players performing training units in the weightlifting halls during the training period, and after that the analysis of the tests was done for the sample examined in the cranes in question.Then the results were presented, analyzed and discussed, and it was concluded that there is an immoral relationship, which confirms that the research sample needs to be followed, as the results reflected a clear weakness of the members of the sample with mental abilities, so the lifters who use their mental abilities well will be positively reflected on the performance of the high net and Snatch And obtaining high achievement, which means that technical and skill performance is related to physical and mental capabilitiesThe researchers recommend that the coaches need to pay attention to mental abilities when following the performance of their players in order to contribute to raising the level of technical and skill performance of the players.